Spinocerebellar ataxia type 2 in a Turkish family - (:unkn) unknown (My University, 2006)
Spinocerebellar ataxias are classified according to the clinical signs, affected neuroanatomical regions and genetic features. Spinocerebellar ataxia type II (SCA 2) is characterized by gait and limb ataxia, dysarthria, ophthalmoplegia, and polyneuropathy . Extrapyramidal system signs and dementia are observed at late clinical stages. SCA 2 is caused by an expanded (CAG) trinucleotide repeat on the chromosome 12 resulting in production of abnormal protein called ataxin-2. Here we report a family who was affected by SCA 2 for three generations. Gait ataxia was the first symptom in all cases, followed by dysarthria and ophthalmoplegia respectively. None of the patients had extrapyramidal signs or cognitive decline. Axonal polyneuropathy was established with EMG in one patient and brain MRI showed pure cerebellar atrophy in all patients. An autosomal dominant cerebellary ataxia was the preliminary diagnosis on the virtue of family history, neurological examination and laboratory and scaning techniques. Genetic studies disclosed a mutation on the SCA 2 locus. Spinocerebellary ataxias are a group of disorders classified according to associating clinical signs and symptoms. Therefore, it is important to establish an accurate clinical classification as it would lead to a clue for the discovery of new gene locuses.
Keywords: Ataxia; Autosomal dominant; Spinocerebellar ataxia